Tendência temporal do índice de massa corporal em alistados do Brasil (1980-2005) - Marra, César Augusto Calembo (2011)
Background: Despite the increasing prevalence of obesity in developed and developing countries, there is little evidence for association between obesity and environmental factors. Objective: To investigate the temporal evolution of BMI in young enlisted men of 18 years in Brazil between 1980 and 2005 to identify specific points of greatest variance in time series and compare specific points in time, the temporal evolution of BMI with socioeconomic changes in Brazil. Methods: The present study explores a temporal series of twenty-six national surveys of Brazilian men who enlisted between 1980 and 2005. Each survey comprises a 35-40% of all Brazilian men aged 18 years at the time of examination. Body weight and height were obtained at the time of medical examination. All measurements were performed by previously trained examiners. Prevalence of overweight and obese men was calculated with 95% confidence intervals. Heteroscedasticity in BMI time series was tested using Engle s Lagrange-multiplier (LM) test, and analyses were performed using the ARCH (1) model with a level of significance set at p < 0.05. For those points in time with higher oscillations of the mean of BMI (1985, 1994 and 2000), dummy variables were included under the assumption that the growth rate of mean BMI was not the same throughout the period. As possible explanations for these increases in mean BMI, changes in economic indicators were considered (Brazilian Institute of Geography and Statistics; and Institute of Applied Economic Research). The economics factors which have been analyzed were: annual inflation rate, food production, poverty (%), soft drinks consumption and average annual real income. Results: The prevalence of overweight men changed from 4.5% in 1980 to 12.5% in 2005 (2.6 times larger) and the prevalence of obesity increased from 0.5% in 1980 to 1.9% in 2005, an increase of almost 300% during the period, but by international comparison they are below average. Particularly in 1985-6 and 1994-5, there was a sharp and significant increase in BMI. In 1985-6, the BMI mean increased from21.4 kg/m2 to 21.5 kg/m2 and in 1994-5, the BMI mean increased from 21.7 kg/m2 to 21.9 kg/m2. These two points (1985-1986 and 1994-1995) occurred after two major economic policy changes that increased the purchasing power of the population. In 1985-6, the changes were mainly related to economic factors such as: reducing the level of social inequality, increased family income, poverty reduction, inflation control, increased time watching television and increased consumption of foods. In 1994-5, in addition to changes in purchasing power, there was a change in the physical activity mandatory in schools. Conclusion: The present study showed a sharp increase of obesity in the population of young men in Brazil on two occasions during this series (years 1985-6 and 1994-5), when a possible reduction in caloric expenditure and increased food consumption population were observed.